2023
DOI: 10.1002/adma.202300396
|View full text |Cite
|
Sign up to set email alerts
|

Chelated Ion‐Exchange Strategy toward BiOCl Mesoporous Single‐Crystalline Nanosheets for Boosting Photocatalytic Selective Aromatic Alcohols Oxidation

Abstract: The photoresponse and photocatalytic efficiency of bismuth oxychloride (BiOCl) are greatly limited by rapid recombination of photogenerated carriers. The construction of porous single‐crystal BiOCl photocatalyst can effectively alleviate this issue and provide accessible active sites. Herein, a facile chelated ion‐exchange strategy is developed to synthesize BiOCl mesoporous single‐crystalline nanosheets (BiOCl MSCN) using acetic acid and ammonia solution respectively as chelating agent and ionization promoter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 76 publications
0
18
0
Order By: Relevance
“…It is intriguing to introduce various boron and nitrogen (G-I) Reproduced with permission. 79 Copyright 2023, Wiley-VCH. (J) SEM, (K) AC-STEM images of BiOCl nanosheets and the corresponding atomograms, where the yellow dashed boxes indicate the locations of some V Bi .…”
Section: Hexagonal Boron Nitridementioning
confidence: 99%
See 2 more Smart Citations
“…It is intriguing to introduce various boron and nitrogen (G-I) Reproduced with permission. 79 Copyright 2023, Wiley-VCH. (J) SEM, (K) AC-STEM images of BiOCl nanosheets and the corresponding atomograms, where the yellow dashed boxes indicate the locations of some V Bi .…”
Section: Hexagonal Boron Nitridementioning
confidence: 99%
“…employed an ion exchange method to craft 15 nm‐thick single‐crystal BiOCl nanosheets, presenting a three‐dimensional layered flower‐like structure (Figure 10G–I). 79 Strong ion coupling led to substantial lattice mismatch, generating abundant high‐density mesopores conducive to rapid charge transport and exceptional catalytic performance. Previous studies have demonstrated that BiOX enriched with vacancy defects is particularly favorable for light absorption 80 .…”
Section: Typical 2d Semiconductor Nanosheetsmentioning
confidence: 99%
See 1 more Smart Citation
“…When the modification of bismuth oxyhalide itself is studied, it is mainly through the introduction of oxygen vacancies and the increase of specific surface area and it is believed that the existence of oxygen vacancies plays a decisive role in the activity of photocatalysts . Oxygen vacancies can enhance the oxidation reduction capacity of catalysts, and large specific surface areas can provide more active sites.…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing aromatic alcohols for the synthesis of high-value-added products, particularly aromatic acids and nitriles, is a crucial aspect of organic chemistry. These fine chemicals are essential precursors for pharmaceuticals, agrochemicals, and dyes . Generally, conventional synthetic routes for aromatic acids and nitriles from aromatic alcohols require homogeneous catalysts or multiple reaction steps. , For instance, aromatic acids prepared by the oxidation of aromatic alcohols require strong oxidants such as NaClO and KMnO 4 , while organic nitriles are typically produced by using poisonous HCN or metal cyanides or under high-temperature and -pressure NH 3 reaction conditions .…”
Section: Introductionmentioning
confidence: 99%